Pengaruh Kreativitas Guru, Lingkungan Belajar dan Motivasi Belajar Terhadap Hasil Belajar - Ginanjar, Yudi; Iskandar, Iskandar; Jumantini, Entin (Peneliti.net, 2024)
This research aims to see the influence of teacher creativity, learning environment and motivation on student learning outcomes in the Business and Management Skills field in the Tasikmalaya Regency Vocational School Business Economics subject. This research uses a survey method with a qualitative and quantitative approach. The population in this study were students at 10 Grade SMK schools in the Business and Management Skills SMK Tasikmalaya Regency. The sampling technique uses a purposive sampling method with Proportionate Stratified Random Sampling type. The instruments used to collect data are questionnaires and documentation. The magnitude of the direct influence of Teacher Creativity (X1) on Learning Motivation (X3) is – 0.051.2. The magnitude of the direct influence of the Learning Environment (X2) on Learning Motivation (X3) is – 0.013. 3. The magnitude of the direct influence of Teacher Creativity (X1) on Learning Outcomes (Y) is 0.341 and the indirect influence of Teacher Creativity (X1) on Learning Outcomes (Y) through Learning Motivation (X3) is - 0.005. With a total influence of 0.336.4. The magnitude of the direct influence of the Learning Environment (X2) on Learning Outcomes (Y) is 0.428 and the indirect influence of the Learning Environment (X2) on Learning Outcomes (Y) through Learning Motivation (X3) is - 0.001. With a total influence of 0.427.5. The magnitude of the direct influence of Learning Motivation (X3) on Learning Outcomes (Y) is 0.099.The research results show that there is an increase in learning outcomes from the documentation of End of Semester Assessment and End of Year Assessment scores which shows an influence on learning outcomes. From the results of calculations and tests that have been carried out, it shows that there is an influence between the Teacher Creativity, Learning Environment and Learning Motivation variables on the Learning Outcome variables, while Teacher Creativity and the Learning Environment directly have no influence on Learning Motivation. Apart from that, Learning Motivation also does not have an influence in mediating Teacher Creativity and the Learning Environment in Business Economics subjects at Tasikmalaya Regency Vocational Schools.